Angiogenin production in response to hypoxia and l‐mimosine in periodontal fibroblasts. Issue 6 (10th January 2019) - Janjić, Klara; Bauer, Peter; Edelmayer, Michael; Cvikl, Barbara; Schädl, Barbara; Moritz, Andreas; Agis, Hermann
Abstract: Background: A major mediator of angiogenesis is angiogenin, which is expressed in the early phase of healing in oral tissue engineering strategies. It is unclear how angiogenin is regulated in the periodontal tissue. The objective of this study was to reveal the regulation of angiogenin in response to hypoxia and the hypoxia mimetic agent l ‐mimosine in periodontal fibroblasts. Methods: Human fibroblasts of the periodontal ligament (PDLF) and the gingiva (GF) in monolayer and spheroid cultures were exposed to hypoxia or l ‐mimosine. The production of angiogenin was evaluated at mRNA and protein levels with reverse transcription quantitative polymerase chain reaction and enzyme‐linked immunosorbent assays, respectively. Echinomycin, an inhibitor of hypoxia‐inducible factor (HIF)‐1 activity, was used to test the involvement of HIF‐1. Results: Our data show that hypoxia and l ‐mimosine can increase angiogenin mRNA and protein levels in PDLF monolayer cultures. In GF monolayer cultures, we found an increase of angiogenin at the mRNA level in response to hypoxia. The increase of angiogenin can be blocked by inhibition of HIF‐1 signaling via echinomycin. In PDLF and GF spheroid cultures, the impact of hypoxia and l ‐mimosine did not reach the level of significance. Conclusion: Hypoxia and the hypoxia mimetic agent l ‐mimosine can increase the production of angiogenin via HIF‐1 signaling in PDLF monolayer cultures but not in spheroid cultures. GF were less sensitive to the impact of hypoxia and l ‐mimosine. Overall, these results suggest a link between hypoxia, HIF‐1 signaling and angiogenin in the periodontium.